A research and development effort in developing the optimal formulations for new tablet drugs using design of experiments: part 1 (dissolution comparisons). (1st January 2012) - Li, Zhe; Cho, Byung Rae; Melloy, Brian J.
Growth in clinical or market demand for tablet drugs often provides the impetus for increasing the scale of production. Pharmaceutical formulation optimisation is conducted initially to find the optimal combination of inactive ingredients, but changes of formulations may occur as consequence of scale-up. In this case, in vitro dissolution comparisons may need to be performed so as to demonstrate the equivalent safety and efficacy of pre-change and post-change formulations. Therefore, formulation optimisation is necessary to determine the levels of composition aimed at ensuring the equivalent safety and efficacy for the changed formulation, while meeting all related regulatory constraints. This article is an attempt to provide a comprehensive formulation optimisation procedure incorporating design of experiments techniques under different levels of scale-up changes in ingredients and biopharmaceutics classifications. Various FDA regulations and evaluation methods are investigated in order to model the optimisation scheme. Numerical examples are given in order to investigate the feasibility of the proposed methodology in solving the formulation optimisation problem for scale-up changes in composition.